Children and Childhood among Evangelical Christians-Baptists During the Late Soviet Period (1960s-1980s) - Panych, Olena (Bogoslovskie razmyšlenija, 2012)
This paper explores strategies and practices of the Christian upbringing of children with in the Evangelical Baptist community during the late Soviet period (1960s11980s). The author depicts three aspects of childhood relationships: the church (congregation), the family and Soviet society. The Evangelical Baptist community treated children as valuable «small followers of Christ.» At the same time, efforts were aimed at bringing children to conversion. The main direction of work with children was to accustom them to prayer and reading Holy Scripture. In their families children were brought up with an understanding of their mother's and father's role differences. The Soviet state strove to limit opportunities for believers and congregations to bring up children in an atmosphere of Christian spirituality. The persecution of parents for violating Soviet religious legislation also influenced their children. Generally, the children of believers were raised in conditions of competition between Evangelical and Soviet atheistic values and often became the subject of manipulation and the struggle for authority and domination. All these circumstances created around them an atmosphere of anxiety and distrust toward the «external» or «worldly» society, and also increased their personal sense of significance.